Pendampingan Pembelajaran Bahasa Arab Melalui Karya Wisata Di Madrasah Ibtidaiyah Miftahul Ulum Jombang - Mz, Isniyatun Niswah; Qomariyah, Lailatul; Setyabudi, M. Arif (Yayasan Kajian Riset Dan Pengembangan Radisi, 2025)
Arabic is one of the subjects given to elementary school students or Madrasah Ibtidaiyah (MI) students. Where Arabic is a separate subject that every week there is. This is a challenge in itself because foreign language teaching is quite complex, one of which must master a lot of vocabulary (Mufrodad). The presence of Arabic learning assistance that focuses on improving students' mufrodad with the tour method and the PAR approach, is expected to provide other colors, new ideas and new insights that can increase students' interest in learning Arabic. The result of this service is an increase in students' mastery of mufrodad. The students are able to apply the mufrodad that has been learned in class and around the school environment, such as recognizing the names of Arabic objects around them.